El Gran Mariscal José de Lamar - Rocafuerte, Vicente. 1783-1847
Contiene artículos escritos por: General O'Leary, José Joaquín de Olmedo, José María Urbina. Antonio Borrero Cortázar. Tomás Rendón. Luis Cordero. Alfonso María Borrero. Remigio Crespo Toral y Carlos Aguilar Vázquez